2000
DOI: 10.1108/00070700010310623
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplement use in later life

Abstract: Describes self-reported dietary supplement use among elderly people in the UK and explores the association between supplement use and socioeconomic, physical and dietary factors. A three-phase survey incorporating face-to-face interviews, self-completed four-day dietary diaries with a food frequency questionnaire and follow-up face-to-face interviews took place in urban Nottingham and rural Nottinghamshire, Lincolnshire and Leicestershire. A total of 957 elderly people (aged over 65) were randomly selected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Consistent with other studies the odds of being a dietary supplement user were significantly higher in people who had school qualifications and post-school qualifications compared with those who did not have any qualifications. 1,9,17,18,22,23 Although supplement users have higher educational levels, the correlation between supplement use and nutrition knowledge has been shown in other studies to be zero 24 or negative. 25 A higher level of education is not necessarily associated with a sound knowledge of nutritional need.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Consistent with other studies the odds of being a dietary supplement user were significantly higher in people who had school qualifications and post-school qualifications compared with those who did not have any qualifications. 1,9,17,18,22,23 Although supplement users have higher educational levels, the correlation between supplement use and nutrition knowledge has been shown in other studies to be zero 24 or negative. 25 A higher level of education is not necessarily associated with a sound knowledge of nutritional need.…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of using a supplement in the previous year was highest in the [15][16][17][18][19][20][21][22][23][24] year age group and the prevalence decreased with increasing age in both males and females. Results from other studies have shown an opposite trend to this with supplement use being lower in the younger adult groups, 2,16 although the data collected in 2000 by MacLennan and colleagues from Australia showed a similar trend with the highest use in the 15-34 year age group.…”
Section: Discussionmentioning
confidence: 99%